The implementation of a core architecture for geophysical data acquisition - Heasman, Ray Edward (Rhodes University, Faculty of Science, Department of Physics and Electronics, 2000)
This thesis describes the design, development and implementation of the core hardware and software of a modular data acquisition system for geophysical data collection. The primary application for this system is the acquisition and realtime processing of seismic data captured in mines. This system will be used by a commercial supplier of seismic instrumentation, ISS International, as a base architecture for the development of future products. The hardware and software has been designed to be extendable and support distributed processing. The IEEE-1394 High Performance Serial Bus is used to communicate with other CPU modules or peripherals. The software includes a pre-emptive multitasking microkernel, an asynchronous mailbox-based message passing communications system, and a functional IEEE-1394 protocol stack. The reasons for the end design and implementation decisions are given, and the problems encountered in the development of this system are described. A critical assessment of the match between the requirements for the project and the functionality of the implementation is made.
Keywords: Geophysics -- Data processing; Computer software -- Development; Seismometers; Computer input-output equipment